2015
DOI: 10.1177/0192623315598578
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Forum Opinion Piece: Carcinogen Risk Assessment

Abstract: Throughout the last 50 years, the paradigm for carcinogenicity assessment has depended on lifetime bioassays in rodents. Since 1997, the International Conference on Harmonisation (ICH) S1B has permitted the use of a 2-year rodent bioassay (usually in the rat) and an alternative, genetically modified mouse model to support cancer risk assessment of pharmaceuticals. Since its introduction, it has become apparent that many of the stated advantages of the 6-month Tg mouse bioassay have, in actual fact, not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…There are reports of in vivo studies, in which OME had effects over increased blood flow of the gastric mucosa and PPIs: proton pump inhibitors; TNF-α: tumor necrosis factor-alpha. 6 Oxidative Medicine and Cellular Longevity expression of gastric glycoproteins [69] that is used as a precise and sensitive marker for the gastric mucosal status. Moreover, OME also plays a significant role as an antiacid, pepsin-resistant, and ulceration protector, which helps to protect the mucosal integrity [81] and reduces neutrophil infiltration [69].…”
Section: Antioxidant and Anti-inflammatory Effects Several In Vivo Smentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of in vivo studies, in which OME had effects over increased blood flow of the gastric mucosa and PPIs: proton pump inhibitors; TNF-α: tumor necrosis factor-alpha. 6 Oxidative Medicine and Cellular Longevity expression of gastric glycoproteins [69] that is used as a precise and sensitive marker for the gastric mucosal status. Moreover, OME also plays a significant role as an antiacid, pepsin-resistant, and ulceration protector, which helps to protect the mucosal integrity [81] and reduces neutrophil infiltration [69].…”
Section: Antioxidant and Anti-inflammatory Effects Several In Vivo Smentioning
confidence: 99%
“…OME, especially for long-term use, may induce DNA damage [6,7]. Genotoxicity assays have been shown that not only OME but all prazoles (e.g., esomeprazole, lansoprazole, pantoprazole, and rabeprazole) can induce chromosomal damages [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in networks between and within human and animal populations account, in part, for interspecies differences and human variability (Meek et al 2014a). Current approaches explore the applicability of the Adverse Outcome Pathway approach (Collier et al 2016; Edwards et al 2016; Zhou 2015) as a framework for linking the initial molecular interactions with the tumour promotion though plausible key events (Becker et al 2015; Downes and Foster 2015). As the EU evaluation concluded that the incidences were due to chance and bias and the evidence does not indicate that glyphosate is an animal carcinogen, no further assessment of relevance for humans was required.…”
Section: Discussionmentioning
confidence: 99%
“…The communication of the outcome of the risk assessment is complex and controversial in the case of equivocal results (Downes and Foster 2015). The identification of a mutagenic or genotoxic mechanism plays an important role in risk assessment and requires a critical evaluation of the data as well as expert judgment (Eastmond 2012).…”
Section: Methodology: Scientific Assessment Of Carcinogenicity and Itmentioning
confidence: 99%
“…Pre-and early post-natal exposure is likely to be critical for carcinogenesis, therefore it is unlikely that the standard RCB (not covering this period) is fully predictive for real life human carcinogenesis (review conclusion in Downes and Foster, 2015).…”
Section: Definition Of the Purpose And Regulatory Relevancementioning
confidence: 99%